The link pediatric history taking and physical examination - Kutty, Prameela Kannan (Jaypee Brothers Medical Publishers (P) Ltd, 2016)
This concise and clearly structured book is divided into 5 sections. The rationale behind taking a child's history is examined first, along with the various types of history that it may be necessary to take. This section includes discussion on pregnancy, delivery, neonatal, breastfeeding and vaccination histories. The book then addresses the approach to, and practicalities of a physical examination